3D gravity anomaly separation method taking into account the gravity response of the inhomogeneous mantle. (1st September 2018) - Liu, Kang; Hao, Tianyao; Yang, Hui; Wen, Baihong; Hu, Weijian; He, Enyuan; Xu, Ya
Graphical abstract: Highlights: Lateral inhomogeneity of the mantle is widespread around the world. Gravity response of inhomogeneous mantle on the Bouguer anomaly cannot be ignored. 3D gravity anomaly separation uses model of "Mantle-Moho-Basement-Sedimentary layer". Abstract: In order to ensure that the gravity data processing and inversion are consistent with the actual geology, we propose that, in integrated geophysical research, 3D gravity anomaly separation (GAS) should take into account the gravity response of the inhomogeneous mantle. This is an effective method by which the residual gravity anomaly (RGA) may be obtained, as well as an important basis for the inversion and interpretation of gravity data. Aimed at the petroliferous basin structure, evolution of continental margin, ocean continental transition zone and other widely discussed geological problems, we extensively investigate the upper mantle structure in many regions around the world, and the results show that the lateral inhomogeneity of the mantle is widespread. In many comprehensive studies based on gravity and seismic data, the gravity anomaly modeling and separation are typically performed within the crust (above the Moho), which actually relies on an assumption of homogeneous mantle. Although this assumption simplifies the difficulty of the gravity modeling and separation, it ignores gravity anomalies caused by inhomogeneities of the deep mantle. The RGA, along with the inverted density structure and other interpretations, involves the risk of deviating from the actual geology. On the basis of the 2D forward calculation of several typical interface models, we implement the quantitative analysis of the effect that the inhomogeneous mantle has on the Bouguer gravity anomaly. In case studies of the southeastern United States and the Sichuan Basin, taking the shear wave velocity ( Vs ) structure of the upper mantle as the constraint condition, we calculate the gravity anomaly caused by the inhomogeneous mantle by means of the forward method. It is found that the gravity response of the inhomogeneous mantle cannot be neglected. Therefore, we conduct 2.5D joint simulation combining gravity and seismic data in the Sichuan Basin. The fitting results after separating the gravity response of the inhomogeneous mantle are clearly superior to those of the homogeneous mantle hypothesis. On the basis of the 3D depth data of several sedimentary strata, the Moho and the mantle high-velocity bodies, we implement 3D GAS, obtain the RGA of the basement in the Sichuan Basin, and discuss the geological origin of the "Dazu high gravity".